3-(3x-8)=4y-5

Simple and best practice solution for 3-(3x-8)=4y-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(3x-8)=4y-5 equation:


Simplifying
3 + -1(3x + -8) = 4y + -5

Reorder the terms:
3 + -1(-8 + 3x) = 4y + -5
3 + (-8 * -1 + 3x * -1) = 4y + -5
3 + (8 + -3x) = 4y + -5

Combine like terms: 3 + 8 = 11
11 + -3x = 4y + -5

Reorder the terms:
11 + -3x = -5 + 4y

Solving
11 + -3x = -5 + 4y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -3x = -5 + -11 + 4y

Combine like terms: 11 + -11 = 0
0 + -3x = -5 + -11 + 4y
-3x = -5 + -11 + 4y

Combine like terms: -5 + -11 = -16
-3x = -16 + 4y

Divide each side by '-3'.
x = 5.333333333 + -1.333333333y

Simplifying
x = 5.333333333 + -1.333333333y

See similar equations:

| (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) | | 3w+5-2w+7= | | 2x^6=-3 | | 5mn-2m(m-2n)= | | 7(x+2)-3x=4(x-1)+10 | | -13.9=b-17.1 | | 3(2n-m)+4m= |

Equations solver categories